Numerical Modelling of One-Way Reinforced Concrete Slab in FireTaking Into Account of Spalling - Guergah Cherif; Dimia Mohamed Salah; Benmarce Abdelaziz (Civil Engineering Journal, 2021)
This paper presents a study of the behaviour of Reinforced Concrete (RC) slabs subjected to severe hydrocarbon fire exposure. In which the spalling phenomena of concrete is to be considered. The hydrocarbon curve is applicable where small petroleum fires might occur, i.e. car fuel tanks, petrol or oil tankers, certain petro-chemical facilities, tunnels, parking structures, etc. Spalling is included using a simplified approach where elements with temperatures higher than 400 °C are assumed to occur and the corresponding thermo-mechanical response of RC slabs is evaluated. The nonlinear finite element software SAFIR has been used to perform a numerical analysis of the spalling risk, by removing layers of concrete covering when a set of spalling criteria is checked. The numerical results obtained by finite element analysis of the temperature distribution within the slab and mid-span deflection were compared with published experimental data. Predictions from the numerical model show a good agreement with the experimental data throughout the entire fire exposure to the hydrocarbon fire. This shows that this approach (layering procedure) is very useful in predicting the behaviour of concrete spalling cases. Doi: 10.28991/cej-2021-03091667 Full Text: PDF